STUDENTS’ PERCEPTION ON THE USE OF SHORT MOVIE IN LEARNING VOCABULARY AT SMP NEGERI 40 MAKASSAR - Setyani, Aini Titah; Ariyani, Amra; Sofyan, Ryan Rayhana (Universitas Negeri Makassar, 2022)
This study aims to determine students' perceptions of the use of short movies in learning vocabulary. The population of this study was students in grade 9 at SMP Negeri 40 Makassar using a purposive sampling technique of 15 students as the sample in this research. This study used descriptive qualitative the researcher used the interview as an instrument. The results of the data show that students have a positive perception of the use of short movies in learning vocabulary. This research is evident from the results of the interviews where they expressed their enthusiasm when watching an English Short Movie. This research also shows the development of students at SMP Negeri 40 Makassar, especially in vocabulary learning.